Aspergillosis of the maxillary sinus as a complication of overfilling root canal material into the sinus: Report of two cases - Khongkhunthian P. (2014)
Aspergillosis of the maxillary sinus is a relatively rare disease in nonimmunocompromised patients. In recent years a number of cases of aspergillosis of the maxillary sinus have been reported in association with overextension of root canals fillings with certain root canal cements. It has been suggested that zinc oxide-based root canal cements might promote the infection with the Aspergillus species. In particular Aspergillus fumigatus has been found to be associated with the maxillary sinus infection. Radiographically the unique appearance of a dense opacity foreign body reaction in the maxillary sinus was considered a characteristic finding in maxillary sinus aspergillosis. Because this association of overfilling of root canal cements and aspergillosis of the maxillary sinus is not too well known we report two cases of young healthy female patients with the characteristic findings, both radiographically and clinically. In both patients the first maxillary molar was involved. Patients were symptomless and the diagnosis was made accidently. However at surgical inspection both patients revealed aspergillomas, including the overextended root canal cement. The surgical procedure is described as are the microscopic findings in both cases showing the characteristic branching hyphae and conidophores typical of Aspergillus. Overextension into the maxillary sinus with root canal cements has to be avoided; material has to be removed from the sinus because otherwise aspergillosis infection may ensue. Copyright © 2001 by The American Association of Endodontists.